Chemical and sensory profiles of rosé wines from Australia. (1st April 2016) - Wang, Jiaming; Capone, Dimitra L.; Wilkinson, Kerry L.; Jeffery, David W.
Highlights: First study on volatiles and aroma/flavour profiles of Australian rosé wines. Quantitative analysis of 47 volatiles was achieved using GC–MS in scan mode. HPLC–MS/MS was applied to quantify 4 polyfunctional thiols. Of 51 volatiles determined, 47 were significantly different among the wines. Four different aroma/flavour profiles are described using 23 sensory descriptors. Abstract: The appeal of rosé wine is attributable to its sensory profiles and underlying chemical composition, which are determined by viticultural and oenological inputs. This study provided the first insight into the sensory attributes and volatile profiles of Australian rosé wines. An HS-SPME–GC–MS method and a recently developed HPLC–MS/MS method were used to quantify 51 volatile compounds, including 4 potent sulfur compounds, in 26 commercial rosé wines. Descriptive analysis on all wines was undertaken and the sensory results were correlated with quantitative chemical data to explore relationships between wine composition and sensory profiles. Based on odour activity values, esters were prominent aroma volatiles, and β-damascenone, 3-methylbutyl acetate, ethyl hexanoate and 3-MHA were deemed to be important, in accord with other studies. Wines were described with terms ranging from developed, spicy and savoury to fresh green, citrus, tropical fruit, floral and confectionery.